Information gaps in the market for social services: Retirement homes in the Czech Republic - Iveta Vrabková; Izabela Ertingerová; Roman Vavrek (Review of Economic Perspectives, 2019)
The research address a partial issue of market failure in the form of information asymmetry. Within the public sector, social services, together with health services, belong to typical sectors where the information superiority of supply against demand is detected. The presence of asymmetrical/imperfect information within the social care has a significant effect on retired people who demand the services of retirement homes, and this effect occurs before as well as during the consumption of this service. The paper aims to identify and evaluate the information gaps of 159 official websites of retirement homes in the Czech Republic that are related to the supply of offered services. The evaluated websites of the retirement homes were selected in a way including all three types of the legal form of retirement homes (semi-budgetary units of regions, limited liability companies, church legal entities) that are present in this category of social services in the Czech Republic. The multi-criteria evaluation, performed by using the TOPSIS method, included 14 types of information (criteria). The TOPSIS method is based on the selection of the variant that is the closest one to the ideal variant and that is characterized by a vector. The results show that retirement homes insufficiently disclose several types of information. These include the conditions of acceptance into the retirement home, annual reports, some types of contact information, internal rules of the home, and the electronic link for the communication with the retirement home. In relation to the evaluation of the total level of 14 types of information being disclosed on the websites of retirement homes, it was revealed that 3% of them achieve an excellent level, 30% achieve a lesser than excellent level, 60% achieve a low level, and 7% of retirement homes achieve a very low level.
Keywords: H41; D82; L33; 330; information asymmetry; multi-criteria evaluation; social service; TOPSIS method; websites of retirement homes